Knowledge, Attitudes, and Behaviors of Pharmacists Towards the Use of Antibiotics: Literature Review - Rosi Hayyu Anjani; Hidayah Karuniawati (Jurnal Indonesia Sosial Teknologi, 2024)
Pharmacists have an important role to play in the safe use of antibiotics and there appears to be no research evaluating pharmacists' knowledge, attitudes, and practices towards antibiotics and antibiotic resistance in Indonesia. An assessment of pharmacists' knowledge, practices and attitudes about antibiotics and their resistance will be useful to identify problems to create effective interventions. The databases used in the literature search are Google Scholar, Pubmed, and ScienceDirect, with inclusion criteria including the year of journal publication from 2010 to 2024, full text, the research sample is pharmacist, the research uses questionnaires, and the method used is cross-sectional, focusing on pharmaceutical knowledge, attitudes, and behaviours on the use of antibiotics. The exclusion criteria include duplication, not full text, inappropriate titles, samples taken that are not pharmacists or included other than pharmacists, only including 1 or 2 of the 3 bound variables, namely knowledge, attitudes, and behaviours, the methods used are not cross-sectional, do not use questionnaires, and files cannot be opened. (n=769) 10 literature met the inclusion criteria, and 8 out of 10 literature stated that sociodemographic factors, namely age, gender, place of residence, employment status, length of work, level of education, and the number of antibiotics administered, affected the knowledge, attitude, and behaviour of pharmacists towards the use of antibiotics without a prescription. 8 out of 10 literature is declared to be of good quality. The results of these 10 kinds of literature for the percentage of pharmacists who have good knowledge are 40%-90% of the sample, the percentage of a good attitude is 50%-90%, and the percentage of good behaviour is 20%-60%. Sociodemographic factors influence the knowledge, attitudes, and behaviours of pharmacists towards the use of antibiotics without prescriptions.